Directing with restraint: Mechanisms of protrusion restriction in collective cell migrations. (September 2022) - Roberto, Gabriela Molinari; Emery, Gregory
Abstract: Cell migration is necessary for morphogenesis, tissue homeostasis, wound healing and immune response. It is also involved in diseases. In particular, cell migration is inherent in metastasis. Cells can migrate individually or in groups. To migrate efficiently, cells need to be able to organize into a leading front that protrudes by forming membrane extensions and a trailing edge that contracts. This organization is scaled up at the group level during collective cell movements. If a cell or a group of cells is unable to limit its leading edge and hence to restrict the formation of protrusions to the front, directional movements are impaired or abrogated. Here we summarize our current understanding of the mechanisms restricting protrusion formation in collective cell migration. We focus on three in vivo examples: the neural crest cell migration, the rotatory migration of follicle cells around the Drosophila egg chamber and the border cell migration during oogenesis.